2020
DOI: 10.3126/jiom.v42i3.37583
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Body Mass Index with Handgrip Strength and Endurance of Dominant Hand in Medical Students

Abstract: Introduction Hand grip strength is used in evaluation of muscle strength and is also increasingly being used as an indicator for nutritional status. The maximum force applied voluntarily by the subject is called maximum handgrip strength, which is measured in kilograms. Muscular endurance is the ability of a muscle or muscle group to perform against a load for an extended period of time, measured in seconds. This study aims to correlate body mass index with handgrip strength and handgrip endurance in medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…But the value of male population was less than the present study. 13 The studies among Indian population reported the value of HGS less than the present study among both male and female. 14,15 HGS shows geographical variation and imposes the need of region specific HGS.…”
Section: Discussioncontrasting
confidence: 74%
“…But the value of male population was less than the present study. 13 The studies among Indian population reported the value of HGS less than the present study among both male and female. 14,15 HGS shows geographical variation and imposes the need of region specific HGS.…”
Section: Discussioncontrasting
confidence: 74%